(3TQM bUjOI GHf QGRcIs - (3YHO Gddg Hf GdWGdH CMeO Hf GdMGL MeGg Gdgd GdZdGhis; (3GHf QGRcIs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3ZQGe (B: (3Ci hdhY Sbi bdHi eOGeg (B: (3NeQ KGfi eaYhdi Sbi UQakG HGdcSQ (B: (3NGdU MGd ef GdeOGeg s
(3BNQgG (B:s
(3SbaG THg Yed GdUMGHI QVi Gddg JYGdi Yfge HGdZQaI HLGeY GdQaY hajg ERGf HGdENJJGe NJe Gddg dfG HGdESdGe HLGg SjO GdCfGe s
(3GdbUjOI ai eOM GdfHi Udi Gddg Ydjg hSdes
(3GdfSNI HgG MhGTs
(3fSNI eQbeI s
(3YdjgG JUMjMGJ s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs